Oral vitamin B1-substitution does not decrease genetically determined cleft rate in mice (A/WySn). Issue 12 (December 2017) - Scheller, Konstanze; Kalmring, Florian; Scheller, Christian; Schubert, Johannes; Bialek, Joanna
Abstract: Purpose: Cleft lip and palate (CL/P) are one of the most common human birth defects. Animal experiments and clinical investigations show a clear reduction of teratogenic clefts by a high-dose vitamin B supplementation during early pregnancy, especially in families at risk (reduction of recurrence). The aim of this work was to examine the influence of thiamine (vitamin B1) on CL/P appearance in genetically determined A/WySn mice within different supplementation starting points. Materials and methods: A total of 24 A/WySn female mice were orally supplemented with high doses (80 mg/kg) of thiamine at different times of pregnancy (5 groups, n = 90). The influence of thiamine on the abortion rate and CL/P appearance in the offspring was analyzed with respect to the concentration of thiamine in the serum and amniotic fluid (HPLC-chromatography). Immunochemical analyses of the ThTr-1 und ThTr-2 receptor-status were performed in midface sections of A/WySn-fetuses and the corresponding placenta, with and without CL/P. Results: High doses of orally supplemented thiamine did not reduce the CL/P appearance in A/WySn mice. However, the different starting points of vitamin B1 substitution had some influence. Additionally, an obvious decrease in aborted fetuses was noticed in all supplemented groups. The oral substitution caused a clear increase of the serum concentration in all mothers, but showed no increase of the amniotic fluid concentration. Then immunohistochemistry detected an overexpression of ThTr-1 in the midface and an irregular localization of ThTr-2 in the placenta of fetuses with clefts. Conclusion: Our results suggest a time-dependent influence of thiamine on CL/P appearance in female mice. The prophylactic/periconceptional, but not the therapeutic supplementation, starting point can be proposed as a crucial step for regular facial and palatal fusion in embryonic development. The absolute rate of CL/P was not reduced, and the concentration of the water-soluble thiamine could not increase in the amniotic fluid. Thus the proposed local effect of thiamine failed in the development of genetically determined mice.